The Response Of The Growth Of Robusta Coffee (Coffea Canephora. L) That Received Treatment Of Time Of Immersion And Concentration Of Sulphic Acid (H2SO4) - Sri Rahmadani Fitri; Azwir Anhar; Linda Advinda; Violita Violita (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Robusta coffee seeds (Coffea canephora L.) require dormancy breaking treatment to accelerate germination. One of the treatments for breaking dormancy that can be done is chemical scarification by adjusting the concentration and duration of sulfuric acid (H2SO4) immersion. This study aims to determine the best concentration (H2SO4) and soaking time for breaking dormancy of robusta coffee seeds. This research was conducted in the Biology laboratory of the Faculty of Mathematics and Natural Sciences, Padang State University, in November-January 2022 using a two-factor completely randomized design. The first factor is the concentration of H2SO4 solution (0%, 10%, 15% and 20%). The second factor is the immersion time (25 minutes, and 50 minutes). Each treatment combination consisted of 4 replications. Parameters observed were germination percentage, germination rate, vigor index, hypocotyl length (cm), root length (cm), and dry weight (grams). The results showed that the H2SO4 concentration treatment had a very significant effect on the percentage of germination parameters, and dry weight while the other parameters had no significant effect. The treatment duration of immersion had a significant effect on the parameters of germination percentage, germination rate, and dry weight while the other parameters had no significant effect. The combination treatment between H2SO4 concentration and soaking time had a very significant effect on the germination rate parameter, significantly affected the germination percentage parameter, and had no significant effect on other parameters.